The Bad Guys in Mission unpluckable - Blabey, Aaron (New York : Scholastic Press, 2016)
Still yearning to be seen as heroes, Wolf, Shark, Snake, and Piranha set out to rescue ten thousand chickens from a high-tech cage farm--but one unexpected problem is Mr. Snake himself, also known as "The Chicken Swallower."
Keywords: Animals -- Juvenile fiction; Rescues -- Juvenile fiction; Chickens -- Juvenile fiction; Heroes -- Juvenile fiction; Animals -- Fiction; Rescues -- Fiction; Chickens -- Fiction; Heroes -- Fiction; Humorous stories; Humorous fiction